1999
DOI: 10.1046/j.1365-2958.1999.01313.x
|View full text |Cite
|
Sign up to set email alerts
|

The assembly and migration of SeqA–Gfp fusion in living cells of Escherichia coli

Abstract: SummarySeqA protein, which binds to hemi-methylated GATC sequences of DNA, is localized to discrete fluorescent foci in wild-type Escherichia coli cells. In this work, we observed cellular localization of the SeqA-Gfp fusion in living cells. SeqA-Gfp was localized to a discrete focus or foci in wild-type and seqA null mutant cells, but the fusion was dispersed in the whole cell in dam null mutant cells lacking Dam methyltransferase. These results were consistent with the previous description of the localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(134 citation statements)
references
References 28 publications
10
124
0
Order By: Relevance
“…Lack of topo IV activity also leads to an increase in the steady-state level of negative supercoiling because of a shift in the balance of topoisomerase activities in the cell (27,28,30,32). SeqA-deficient strains exhibit aberrant nucleoid formation, abnormal segregation of chromosomal DNA, and an increased steady-state level of negative superhelicity (11)(12)(13)(14)17). These until now unexplained parC-and parE-like phenotypes of seqA mutants might be explained by the results we are reporting here, namely that the SeqA protein is required for proper activity of the topo IV enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of topo IV activity also leads to an increase in the steady-state level of negative supercoiling because of a shift in the balance of topoisomerase activities in the cell (27,28,30,32). SeqA-deficient strains exhibit aberrant nucleoid formation, abnormal segregation of chromosomal DNA, and an increased steady-state level of negative superhelicity (11)(12)(13)(14)17). These until now unexplained parC-and parE-like phenotypes of seqA mutants might be explained by the results we are reporting here, namely that the SeqA protein is required for proper activity of the topo IV enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Strains with seqA mutations exhibit aberrant nucleoid distribution, a higher frequency of anucleoid cells, and filamentation (11)(12)(13)(14). Microscopy of immunolabeled or green fluorescent protein-tagged SeqA has revealed that SeqA is predominantly localized in foci situated at the replication forks, presumably forming complexes with the newly replicated DNA and possibly contributing to proper segregation of daughter chromosomes (4,11,15,16).…”
mentioning
confidence: 99%
“…The SeqA protein of E. coli binds to newly replicated DNA via interactions with hemimethylated GATC sites that are produced after DNA replication and can be seen as foci colocalized with the replisome (Onogi et al, 1999;Brendler et al, 2000). Aggregation of SeqA protein has been proposed to organize the chromosome into a filamentous structure after passage of the replication fork (Han et al, 2003;Han et al, 2004).…”
Section: Seqa Foci Are Perturbed In Obge-depleted Cellsmentioning
confidence: 99%
“…Note that B. subtilis does not have SeqA or methylation at GATC sites (Kunst et al 1997). SeqA forms either one centrally located focus or two foci, one in each half of the cell, and focus formation depends on the GATC methylase Onogi et al 1999) and DNA replication . Although SeqA also specifically binds to the origin or replication (Slater et al 1995), SeqA foci do not appear to colocalize with oriC ).…”
Section: A Central Replication Factorymentioning
confidence: 99%